Bat flies in some localities of the Peruvian coast - Bonifaz, Emilio (2020)
There are at least 180 species of bats in Peru. However, there are few studies about ectoparasites of bats, among which the so-called bat flies (Diptera: Streblidae and Nycteribiidae) stand out, with a total of 158 species estimated for the Neotropical region. In Peru, one of the ecological regions with the least information is the coast. In this study we updated the knowledge of the ectoparasite-host associations in bats from the Peruvian coast, one of the regions of the country with the most degradation and loss of habitat. Five locations in the Piura, Lima and Tacna regions were evaluated. 85 bats belonging to 7 species were captured: 4 from Phyllostomidae, 2 from Molossidae and 1 from Vespertilionidae. Six dipterous species (Diptera: Streblidae) and one Hemiptera species (Hemiptera: Polyctenidae) were found and some of these associations are reported for the first time in the Lima and Piura regions. Anoura peruana is also reported as the host of Anastrebla modestini (Streblidae) in a reproductive colony shared with Platalina genovensium, and for the first time for the Piura region, the co-parasitism of the Megistopoda aranea, Aspidoptera phyllostomatis and Metelasmus pseudopterus in a same individual of Artibeus fraterculus.